Epidemiological factors associated with recent HIV infection among newly-diagnosed cases in Singapore, 2013-2017 - Li Wei Ang; Carmen Low; Chen Seong Wong; Irving Charles Boudville; Matthias Paul Han Sim Toh; Sophia Archuleta; Vernon Jian Ming Lee; Yee Sin Leo; Angela Chow; Raymond Tzer-Pin Lin (BMC, 2021)
Abstract Background Early diagnosis is crucial in securing optimal outcomes in the HIV care cascade. Recent HIV infection (RHI) serves as an indicator of early detection in the course of HIV infection. Surveillance of RHI is important in uncovering at-risk groups in which HIV transmission is ongoing. The study objectives are to estimate the proportion of RHI among persons newly-diagnosed in 2013-2017, and to elucidate epidemiological factors associated with RHI in Singapore. Methods As part of the National HIV Molecular Surveillance Programme, residual plasma samples of treatment-naïve HIV-1 positive individuals were tested using the biotinylated peptide-capture enzyme immunoassay with a cutoff of normalized optical density ≤ 0.8 for evidence of RHI. A recent infection testing algorithm was applied for the classification of RHI. We identified risk factors associated with RHI using logistic regression analyses. Results A total of 701 newly-diagnosed HIV-infected persons were included in the study. The median age at HIV diagnosis was 38 years (interquartile range, 28-51). The majority were men (94.2%), and sexual route was the predominant mode of HIV transmission (98.3%). Overall, 133/701 (19.0, 95% confidence interval [CI] 16.2-22.0%) were classified as RHI. The proportions of RHI in 2015 (31.1%) and 2017 (31.0%) were significantly higher than in 2014 (11.2%). A significantly higher proportion of men having sex with men (23.4, 95% CI 19.6-27.6%) had RHI compared with heterosexual men (11.1, 95% CI 7.6-15.9%). Independent factors associated with RHI were: age 15-24 years (adjusted odds ratio [aOR] 4.18, 95% CI 1.69-10.31) compared with ≥55 years; HIV diagnosis in 2015 (aOR 2.36, 95% CI 1.25-4.46) and 2017 (aOR 2.52, 95% CI 1.32-4.80) compared with 2013-2014; detection via voluntary testing (aOR 1.91, 95% CI 1.07-3.43) compared with medical care; and self-reported history of HIV test(s) prior to diagnosis (aOR 1.72, 95% CI 1.06-2.81). Conclusion Although there appears to be an increasing trend towards early diagnosis, persons with RHI remain a minority in Singapore. The strong associations observed between modifiable behaviors (voluntary testing and HIV testing history) and RHI highlight the importance of increasing the accessibility to HIV testing for at-risk groups.